Phytochemical profile, antioxidant and anti proliferative studies in different extracts of Artocarpus kemando miq. bark - Noor Shafifiyaz Mohd Yazid,; Najihah Mohd Hashim,; Hapipah Mohd Ali,; Rusea Go, (Penerbit Universiti Kebangsaan Malaysia, 2021)
In this study, the stem bark of Artocarpus kemando was used to find alternative antioxidants from natural sources with fewer side effects. A. kemando was extracted successively using hexane, chloroform and methanol solvents, and evaluated for antioxidant, cytotoxic, and antiproliferative activities. The extracts were investigated for determination of their total phenolic content (TPC) and total flavonoid content (TFC). Then, the antioxidant activities were evaluated using chemical based assays such as ferric reducing antioxidant power (FRAP), total antioxidant capacity, radical scavenging of 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) and 2,2’-azino-bis (3-ethylbenzothia zoline-6-sulphonic) (ABTS), β-carotene-linoleic acid (BC) assay, oxygen radical absorbance capacity (ORAC), and cell based assay. The cytotoxic study was done using four different cell lines namely human estrogen receptor positive (ER+) breast cancer cell line (MCF7), human ovarian cancer cell line (CAOV-3), human promyelocytic leukemia cell line (HL60), and normal immortalised human ovarian surface epithelial cell line (TI074), and were evaluated using microculture tetrazolium salt (MTT) before morphological change study was done on CAOV-3 cell. In this study, methanol extract displayed the most promising antioxidant activity compared to other extracts when tested with DPPH, FRAP, ABTS, TAOC, BC, ORAC, and cytoprotective assays. The remarkable activity showed by the methanol extract might be due to its high content of phenolic and flavonoid compounds at 855.5 ± 0.01 GAE µg/mL and 145.45 ± 0.06 QAE µg/mL, respectively. Nevertheless, the chloroform extract displayed better scavenging activity compared to other extracts with IC50 value of 618 ± 0.04 µg/mL in DPPH assay. Each extract was analysed using Gas Chromatography Mass Spectrophotometry and the chemical constituents obtained were then analysed. In the cytoprotective activity, the methanol extract showed a comparable cytoprotection with ascorbic acid against the free radicals at the lowest effective concentration (EC50) value of 21.48 µg/mL. However, in the cytotoxicity study, only chloroform extract displayed significant toxicity against the cancer cells with IC50 value of 27.9 ± 0.03, 24.1 ± 0.02 and 9.0 ± 0.04 µg/mL after treatment at 24, 48, and 72 h, respectively. The chloroform extract of A. kemando was found capable of inducing apoptosis as shown with cell membrane blebbing, chromatin condensation and formation of apoptotic bodies. The results obtained from the study showed that A. kemando bark could be a potential antioxidant and antitumor agents particularly on human ovarian cancer cells.